2020
DOI: 10.3390/chemistry2020033
|View full text |Cite
|
Sign up to set email alerts
|

The Photophysical Properties of Triisopropylsilyl-ethynylpentacene—A Molecule with an Unusually Large Singlet-Triplet Energy Gap—In Solution and Solid Phases

Abstract: The process of singlet-exciton fission (SEF) has attracted much attention of late. One of the most popular SEF compounds is TIPS-pentacene (TIPS-P, where TIPS = triisopropylsilylethynyl) but, despite its extensive use as both a reference and building block, its photophysical properties are not so well established. In particular, the triplet state excitation energy remains uncertain. Here, we report quantitative data and spectral characterization for excited-singlet and -triplet states in dilute solution. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(47 citation statements)
references
References 66 publications
14
33
0
Order By: Relevance
“…Our results accord with those of Schaberle et al, who report essentially unchanged emission spectra for TPn in toluene up to a concentration of 50 mM. 22 The lack of concentration-dependent emission spectra at longer wavelengths also accords with the results of Walker et al 14 and Grieco et al 20 Absorption spectra are also unchanged up to 30 mM (see SI), also demonstrated by Schaberle et al in toluene. 22 Immediate evidence of singlet fission in this experiment comes from the concentration-dependent photoluminescence quantum yield (Φ P L ).…”
Section: Steady-state Spectroscopysupporting
confidence: 92%
See 3 more Smart Citations
“…Our results accord with those of Schaberle et al, who report essentially unchanged emission spectra for TPn in toluene up to a concentration of 50 mM. 22 The lack of concentration-dependent emission spectra at longer wavelengths also accords with the results of Walker et al 14 and Grieco et al 20 Absorption spectra are also unchanged up to 30 mM (see SI), also demonstrated by Schaberle et al in toluene. 22 Immediate evidence of singlet fission in this experiment comes from the concentration-dependent photoluminescence quantum yield (Φ P L ).…”
Section: Steady-state Spectroscopysupporting
confidence: 92%
“…Total-internal reflection excitation showed that the emission spectrum is unchanged over a range up to 28 mM, and as such there are no observable, emissive excimers present. This contrasts strongly with the findings of Walker et al whose emission spectra suffered severe reabsorption, 14 but accords with results obtained in toluene by Schaberle et al 22 NMR experiments confirmed that aggregation occurs in TPn solutions. At the highest concentrations employed spectroscopically, only a few percent of chromophores are present as dimers, and there are hints of this in the observed transient absorption.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Due to their high tunability, PAHs and their derivatives are also particularly suitable for more intricate applications such as logic gates [7], single molecule conductance [8,9], thermoelectrics [10], and multi-stage redox systems [11]. Ever more intricate PAH structures are being synthesised [12,13] and ever more detailed spectroscopic experiments performed [14][15][16].…”
Section: Introductionmentioning
confidence: 99%